Dispersion effect on a lead–zinc sulphide ore flotation. - Silvestre, Marcelo Oliveira (2009)
This investigation was performed with samples from a lead–zinc sulphide deposit aiming at studying the influence of the dispersion degree of the particles in the pulp on lead and zinc flotation. Samples of ore and also of the minerals sphalerite, galena, pyrite, and dolomite were selected for the experiments. Nine types of dispersing agents and six blends among them were employed. A set of three dispersing agents was selected for the lead flotation and another set of three was chosen for zinc flotation. The criteria for the reagents selection were: high dispersion degree for galena and low for the other species, high dispersion degree for sphalerite and low for the other species, low dispersion degree for pyrite and high for the other species, and high dispersion degree for all species. Lead flotation experiments were performed under three conditions aiming at verifying the influence of the dispersing agent, of the pH, and of sodium carbonate. The zinc flotation tests were carried out at pH 10.5, modulated with lime. The use of dispersing agents in lead flotation did not improve the overall efficiency of the circuit for, despite improving the lead metallurgical recovery, they increase significantly the zinc losses in the lead concentrate. Sodium carbonate presented a low dispersion degree and did not affect the lead flotation results when compared with those achieved at natural pH and at pH 9.8 modulated with lime. Two dispersing agents were particularly effective in zinc flotation: dispersant 3223, a sodium polyac-rylate, and sodium hexametaphosphate. Both reagents significantly enhanced zinc recovery without impairing the concentrate quality.